(untitled) (Rajarshi Janak University Research Journal, 2025)
Technology is taking over the world in every sector nowadays, including education. In such a context, this study explores the roles of technology in optimizing English language learners’ classroom engagement. It followed narrative inquiry as a research method, considering that non-numerical discursive data support exploring such phenomena. In this study, the data were collected from four purposively selected participants through interview techniques using interview guidelines as the data collection tools. This study revealed that teachers face challenges in ICT integration in school education because of insufficient expertise, a lack of collaborative culture among educators, and inadequate training related to technology integration. This study can be beneficial for those who are interested in exploring technology-integrated education.